Equitable musical-aesthetic practice in elementary school: An explorative approach to mapping a complex phenomenon - Oravec, Lina; Schmid, Silke (Beiträge empirischer Musikpädagogik, 2024)
In the German-speaking disciplinary discourse on music education, there is general consensus regarding the relevance of musical-aesthetic practice as a fundamental characteristic of music education. However, relevant publications of the discipline-specific aesthetic discourse often focus on secondary education, the perspective on elementary school students is currently underrepresented. The emphasis on aesthetic argumentation is particularly in conflict with an inclusive understanding of aesthetic practice in the context of elementary school. Against this backdrop, the article brings together perspectives specific to elementary school and children's music education as well as interdisciplinary approaches that explicitly refer to or can be meaningfully related to the aesthetic paradigm. In doing so, we elaborate on dimensions that complement Schmid's (2016) four dimensions of embodiment, narrativity, materiality, and sociality with the dimensions of play, multimodality, spatiality, and agency. These dimensions appear particularly worthy of consideration in examining aesthetic practice in elmentary education – both in theory formation and educational practice, and potentially in empirical research as well.